Visualizing climate change in the Arctic and beyond: Participatory media and the United Nations Conference of the Parties (COP), and interactive Indigenous Arctic media. Issue 1 (1st January 2020) - MacKenzie, Scott; Stenport, Anna Westerstahl
Impactful communication remains a vexing problem for climate science researchers and public outreach. This article identifies a range of moving images and screen-based media used to visualize climate change, focusing especially on the Arctic region and the efforts of the United Nations. The authors examine the aesthetics of big data visualization of melting sea ice and glaciers made by NASA and similar entities; eye-witness, expert accounts and youth-produced documentaries designed for United Nations delegates to the annual COP events such as the Youth Climate Report; Please Help the World, the dystopian cli-fi narrative produced for the UN's COP 15; and Isuma TV's streaming of works by Indigenous practitioners in Nunavut.